Apoptose em placenta de mulheres com e sem hipótese de infecção por Streptococcus agalactiae - Lais de Lima Franco (2009)
Recent advances in Obstetrics and Neonatology improved the attendance to the pregnant and newborn, identifying factors that raise maternal and fetal morbi-mortality. Amongst the main risk factors for neonatal sepsis are the premature parturition and the premature rupture of membranes, which increases the chances of maternal colonization by the Group B Streptococcus. These bacteria may appear in up until 30% of the pregnants, and its prevalence is estimated at the endocérvix in between 9% and 14%. Placental maturation is an intrinsic part of the tissue development during pregnancy. Apoptosis seems to have a critical role in different stages of placental development, in the interstitial and endovascular invasion and in the maternal immunological tolerance to the different invading microorganisms. The objective of this paper was to study the occurrence of apoptosis as a factor of maturation in 24 placentas of women with (12) and without (12) hypothesis of infection for Streptococcus sp through molecular (Polimerase Chain Reaction using primers to Streptococcus agalactiae) and morphometrical (Quantification of cellular apoptosis) approaches. Quantification of apoptotic cells did not show differences between streptococcus colonized placentas (53,03 ± 1,629) and control placentas (52,64 ± 1,603), although qualitatively more frequent apoptosis was found around bacterial clusters. Several factors seem to interfere with placental apoptosis, increasing or decreasing the turnover in infected placenta: gestational age, parturition, rupture of the membranes, maternal immunity, symptomatology and also quantity of bacteria.